Health care utilisation two years prior to suicide in Sweden: a retrospective explorative study based on medical records - Erik Bergqvist; Sara Probert-Lindström; Elin Fröding; Nina Palmqvist-Öberg; Anna Ehnvall; Charlotta Sunnqvist; Tabita Sellin; Marjan Vaez; Margda Waern; Åsa Westrin (BMC, 2022)
Abstract Objective Previous literature has suggested that identifying putative differences in health care seeking patterns before death by suicide depending on age and gender may facilitate more targeted suicide preventive approaches. The aim of this study is to map health care utilisation among individuals in the two years prior to suicide in Sweden in 2015 and to examine possible age and gender differences. Methods Design: A retrospective explorative study with a medical record review covering the two years preceding suicide. Setting: All health care units located in 20 of Sweden's 21 regions. Participants: All individuals residing in participating regions who died by suicide during 2015 (n = 949). Results Almost 74% were in contact with a health care provider during the 3 months prior to suicide, and 60% within 4 weeks. Overall health care utilisation during the last month of life did not differ between age groups. However, a higher proportion of younger individuals (< 65 years) were in contact with psychiatric services, and a higher proportion of older individuals (≥ 65 years) were in contact with primary and specialised somatic health care. The proportion of women with any type of health care contact during the observation period was larger than the corresponding proportion of men, although no gender difference was found among primary and specialised somatic health care users within four weeks and three months respectively prior to suicide. Conclusion Care utilisation before suicide varied by gender and age. Female suicide decedents seem to utilise health care to a larger extent than male decedents in the two years preceding death, except for the non-psychiatric services in closer proximity to death. Older adults seem to predominantly use non-psychiatric services, while younger individuals seek psychiatric services to a larger extent.